The Influence of Vulva Hygiene Health Education using the Gallery Walk Method on the Ability to Treatment of Leuchorrhoea in Boarding Schools - Fisca Benny Nazza; Yuni Puji Widiastuti; Muhammad Khabib Burhanudin Iqomh (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Vulva hygiene is an individual effort to maintain the cleanliness of the private area which all women should do. But not all women, especially young women are able to do it properly and correctly. The prevalence of leucorrhoea management in adolescents in Islamic boarding schools shows that 51.3% of students do not manage it properly. One effort to increase knowledge and change adolescent behavior is by providing health education using the gallery walk method. The purpose of this study was to determine the influence of vulva hygiene health education using The gallery Walk method on the ability to treatment of leucorrhoea In boarding schools. this research is a quasi-experimental design type of One Group Pre-Post Test Design Without Control Group, the population is 52 respondents with a total sampling technique. Results: the research shows that the age characteristics of the majority of respondents are 16 years old and the majority are from class X (46.2%). After conducting health education using the gallery walk method, knowledge increased (9.5%), attitudes increased (100%), and abilities increased (96.2%). The results of statistical tests using Chi Square showed that there was an influence of vulva hygiene health education using the gallery walk method on the ability to manage leucorrhoea at the Darul Muqorrobin Islamic Boarding School with a probability value of 0.05.